Aesthetics of Virtual: The Development Opportunities of Virtual Museums in Indonesia - Ayu Soraya; Yusup Sigit Martyastiadi (Graduate School of Institut Seni Indonesia Yogyakarta, 2021)
The Covid-19 pandemic requires us to carry out physical and social distancing. It is undeniable, this also has an impact on government policy to close tourist destinations, including museums. Currently, sophisticated 3D visualization technology provides the potential for the development of virtual museums. The virtual museums were developed for giving the experience of the visiting museum in the digital world as a distance learning. This application can provide immersion through interactivity while exploring virtual museums. Basically, this article explains the aesthetic investigations in some virtual museums. The researchers describe the aesthetic of each sampled virtual museums projects. The literature synthesis of several virtual museums projects is expected to be able to give an idea of the potential development of virtual museums in Indonesia. The aesthetics of virtual elements could be used as a recommendation for museum conservator for the development of prospective Indonesian virtual museums. Furthermore, the aesthetics of virtual in digital museums provide opportunities to present virtual museums exploration experiences. Estetika Virtual: Peluang Perkembangan Museum Virtual di IndonesiaAbstrakPandemi Covid-19 mengharuskan kita melakukan jarak fisik dan sosial. Tak bisa dipungkiri, hal ini juga berdampak pada kebijakan pemerintah untuk menutup destinasi wisata, termasuk museum. Saat ini, teknologi visualisasi 3D yang canggih memberikan potensi untuk pengembangan museum virtual. Museum virtual dikembangkan untuk memberikan pengalaman mengunjungi museum di dunia digital sebagai pembelajaran jarak jauh. Aplikasi ini dapat memberikan immersion melalui interaktivitas sambil menjelajahi museum virtual. Pada dasarnya, artikel ini menjelaskan investigasi estetika di beberapa museum virtual. Para peneliti mendeskripsikan estetika dari setiap proyek museum virtual yang dijadikan contoh. Sintesis literatur dari beberapa proyek museum virtual diharapkan dapat memberikan gambaran tentang potensi perkembangan museum virtual di Indonesia. Estetika unsur virtual dapat dijadikan sebagai rekomendasi bagi konservator museum untuk pengembangan museum virtual Indonesia yang akan datang. Selain itu, estetika virtual dalam museum digital memberikan peluang untuk menghadirkan pengalaman eksplorasi museum virtual.